Studies in the Eighteenth Century Background of Hume's Empiricism - Kuypers, Mary Shaw, 1891- (Book collections on Project MUSE., 1930)
Studies in the Eighteenth Century Background of Hume's Empiricism was first published in 1930. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. A scholarly review of the influence of contemporary science and thought on the various phases of Hume's philosophy. The chapter headings are as follows: I. Introduction. II. Interpretations of Newtonian Science in the Eighteenth Century. III. Reverberations of the New Science in Philosophy. IV. Hume's Empiricism in Relation to Contemporary Science and Philosophy. V. Empiricism in Morals. VI. Empiricism in Politics. VII. Hume's Historical Writing. Bibliography.